IoT Based Digital Weight Scale in Rice Inventory for Small and Medium Entreprises - Assidiq, Muhammad; Yelfianhar, Ichwan; Mirshad, Emilham (Department of Electrical Engineering Universitas Negeri Padang, 2024)
In the current digital era, Internet of Things (IoT) technology offers innovative solutions to increase efficiency and accuracy in various sectors, including the rice sales business. This journal discusses the design of IoT-based scales specifically designed to help with bookkeeping in rice sales businesses. The main objective of this research is to develop a weighing system that can automatically measure the weight of rice and integrate it with a digital bookkeeping system, thereby minimizing manual errors and increasing operational efficiency. The research methodology includes design of weighing hardware and software, implementation of weight sensors, and development of IoT applications that connect scales with bookkeeping systems. The system is designed to send real-time weight data to a cloud-based bookkeeping platform, enabling more accurate and faster monitoring and reporting. Test results show that this IoT-based scale can provide weight data with high accuracy and seamless integration with the bookkeeping system. Users report increased efficiency in the process of recording and managing rice sales data. In conclusion, IoT-based scales offer an effective solution for modernizing the bookkeeping process in rice sales businesses, supporting better decision making and improving the accuracy of financial reports.